2014
DOI: 10.1111/spc3.12131
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting External Validity: Concerns about Trolley Problems and Other Sacrificial Dilemmas in Moral Psychology

Abstract: Sacrificial dilemmas, especially trolley problems, have rapidly become the most recognizable scientific exemplars of moral situations; they are now a familiar part of the psychological literature and are featured prominently in textbooks and the popular press. We are concerned that studies of sacrificial dilemmas may lack experimental, mundane, and psychological realism and therefore suffer from low external validity. Our apprehensions stem from three observations about trolley problems and other similar sacri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
204
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 273 publications
(227 citation statements)
references
References 81 publications
3
204
0
2
Order By: Relevance
“…To more fully capture these underlying psychological differences between war and peace contexts, future studies could employ a process dissociation approach (Conway & Gawronski, 2013), or investigate a broader range of outcomes, including for example affective reactions to harm, or concern for moral rules in war. One implication of these findings is that some caution may be warranted when making generalizations to morality writ large on the basis of war-related scenarios (see also Bauman, McGraw, Bartels, & Warren, 2014;Bloom, 2011). In the present studies we found that the intergroup nature of war influenced people's moral judgments about harm in war-even if they belonged to neither of the two groups actually at war-and that the usually robust difference between switch and footbridge scenarios was attenuated in the war context.…”
supporting
confidence: 50%
“…To more fully capture these underlying psychological differences between war and peace contexts, future studies could employ a process dissociation approach (Conway & Gawronski, 2013), or investigate a broader range of outcomes, including for example affective reactions to harm, or concern for moral rules in war. One implication of these findings is that some caution may be warranted when making generalizations to morality writ large on the basis of war-related scenarios (see also Bauman, McGraw, Bartels, & Warren, 2014;Bloom, 2011). In the present studies we found that the intergroup nature of war influenced people's moral judgments about harm in war-even if they belonged to neither of the two groups actually at war-and that the usually robust difference between switch and footbridge scenarios was attenuated in the war context.…”
supporting
confidence: 50%
“…Most importantly, along with other recent studies (Bauman et al, 2014;Kahane et al, 2015), our findings cast further doubt on the status of standard sacrificial dilemmas as valid measurements of moral preferences. Put simply, if respondents are not unambiguously more sensitive to Moral Code than they are to Action, it is doubtful that one can rely upon standard sacrificial dilemmas to draw inferences about who is more "utilitarian" (and under what circumstances).…”
Section: Implications and Future Researchsupporting
confidence: 54%
“…Although sacrificial dilemma responses are frequently still framed as "utilitarian" or "deontological" choices (Lee & Gino, 2015), recent studies suggest that responses to sacrificial dilemmas do not correlate with other variables in ways expected of a measure of utilitarian versus deontological preferences (Bartels & Pizarro, 2011;Bauman, McGraw, Bartels, & Warren, 2014;Duke & Bègue, 2015;Kahane, Everett, Earp, Farias, & Savulescu, 2015;Rosas & Koenigs, 2014). We aim to further this line of research by addressing a largely unexamined issue concerning the construct validity of sacrificial dilemmas: the confounding of the endorsement of utilitarian outcomes with the endorsement of action.…”
Section: Introductionmentioning
confidence: 99%
“…Although some have argued that experimental analyses of the trolley problem suffer from low external validity, and the early work has uncovered a wide range of results, projects like these aptly demonstrate the inconsistencies in participants' ethical reasoning and the need to think carefully about the ethical challenges of forced-choice algorithms. 53 As public health experts think about forced-choice scenarios, concerns for fairness, equity, and informed choice should lead to discussions about the possible difference between a pedestrian-who is literally an innocent bystander-and the occupants of an autonomous vehicle-who have voluntarily climbed aboard. By choosing to ride in an autonomous vehicle, passengers have access to a level of safety and convenience that is unparalleled in other forms of transportation.…”
Section: 52mentioning
confidence: 99%